Aplikasi Pelaporan Kelebihan Jam Mengajar Jurusan Akuntansi PNP - Sukartini; Surya, Firman; Haslina, Welsi; Yusnani; Maryati, Ulfi (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
This study aims to create a database application program that is able to process data on lecturer course activities and generate reports on the calculation of teaching fees periodically during the pandemic which requires lecturers to report lecture activities online. The system design method approach used is prototyping, namely by creating a program that most closely resembles user needs in a relatively short time. The prototype was generated using the Microsoft Access 2010 database application. The selection of microsoft access to create a prototype was based on the availability of complete facilities in Microsoft Access to design table relations, input forms, query processing, reports and the visual basic programming language for applications. Google Forms used to receive lecture data input online. The application development stages consist of design, testing and implementation stages. This application has succeeded in providing the right solution for the Padang State Polytechnic Accounting Department during the pandemic in calculating and reporting lecture activities and lecturers teaching fees.